PERAN HUMAS KORPS DA’I DEWAN MASJID INDONESIA DALAM MELAKSANAKAN KEGIATAN BHAKTI SOSIAL - Nurrachim, Marye Vaya (Universitas Mercu Buana, 2016)
The role of public relations in designing social bhakti activities to get a positive image of the community is a top priority for this organization. Here the researcher tries to examine how the public relations role of the Corps of Da'i Dewan Masjid Indonesia in succeeding the implementation of social welfare bhakti activities and the distribution of basic needs. Four public relations roles are Communication Technician, Communication Facilitator, Expert Advisor, and Problem Solving Facilitator. This research uses descriptive research type, and qualitative research method of case study by conducting in-depth interview to some resource and observation as well as some supporting documents. Based on the result of the research, it can be concluded that the role of public relations officer of Da'i Council of Mosque of Indonesia in social activities of orphanage donation and the distribution of basic foods, the role of public relations done by focusing on the role of communication technician (Communication Technician) and Communication Facilitator. Peran humas dalam merancang kegiatan bhakti sosial untuk mendapatkan citra positif dari masyarakat adalah prioritas utama bagi organisasi ini. Disini peneliti mencoba untuk meneliti bagaimana peran humas Korps Da’i Dewan Masjid Indonesia dalam mensukseskan pelaksanaan kegiatan bhakti sosial santunan yatim dan pembagian sembako tersebut. Empat peran humas yaitu Teknisi Komunikasi, Fasilitator Komunikasi, Penentu Ahli, dan Fasilitator Pemecah masalah. Penelitian ini menggunakan tipe penelitian deskriptif, dan metode penelitian kualitatif studi kasus dengan melakukan wawancara mendalam kepada beberapa nara sumber dan observasi serta beberapa dokumen pendukung. Berdasarkan hasil penelitian, diperoleh kesimpulan peran yang dilakukan humas Korps Da’i Dewan Masjid Indonesia dalam kegiatan bhakti sosial santunan yatim dan pembagian sembako, peran humas yang dilakukan dengan menitikberatkan kepada peran sebagai teknisi komunikasi (Technician Communication) dan Fasilitator komunikasi (Communication Facilitator).